2011
DOI: 10.2147/ijn.s18507
|View full text |Cite
|
Sign up to set email alerts
|

Nano-zinc oxide damages spatial cognition capability via over-enhanced long-term potentiation in hippocamus of Wistar rats

Abstract: This study focused on the effects of zinc oxide nanoparticles (nano-ZnO) on spatial learning and memory and synaptic plasticity in the hippocampus of young rats, and tried to interpret the underlying mechanism. Rats were randomly divided into four groups. Nano-ZnO and phosphate-buffered saline were administered in 4-week-old rats for 8 weeks. Subsequently, performance in Morris water maze (MWM) was determined, and then long-term potentiation (LTP) and depotentiation were measured in the perforant pathway to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 36 publications
(27 reference statements)
3
18
0
Order By: Relevance
“…But it was observed that ZnOPC treatment was not able to significantly reverse the scopolamine induced memory deficit. This is in well agreement with past study, which revealed chemically synthesized ZnONP damages the spatial learning and memory capability in rats through disruptive effect at the homeostasis of synaptic Zn concentration leading to direct hyperactive long-term potentiation and insufficient depotentiation in hippocampus ( Han et al, 2011 ). In contrast to these results, it has also been reported that no steady difference was observed in emotional behavior of ZnOPC treated rats via EPM as compared to control group ( Xie et al, 2012 ).…”
Section: Discussionsupporting
confidence: 93%
“…But it was observed that ZnOPC treatment was not able to significantly reverse the scopolamine induced memory deficit. This is in well agreement with past study, which revealed chemically synthesized ZnONP damages the spatial learning and memory capability in rats through disruptive effect at the homeostasis of synaptic Zn concentration leading to direct hyperactive long-term potentiation and insufficient depotentiation in hippocampus ( Han et al, 2011 ). In contrast to these results, it has also been reported that no steady difference was observed in emotional behavior of ZnOPC treated rats via EPM as compared to control group ( Xie et al, 2012 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, no significant changes in locomotor activity or exploratory behavior were identified. ZnO NPs have been demonstrated to damage spatial cognition capability via over-enhanced long-term potentiation in the hippocampus of Wistar rats 15 . However, Xie et al reported that ZnO NPs ameliorated behavioral and cognitive impairments in Swiss male mice with depressive-like behaviors induced by LPS 50 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more and more researches have provided evidence that NPs can reach the brain via blood-brain barrier (BBB) penetration or translocation along the olfactory nerve pathway and subsequently cause damage by the induction of oxidative stress, inflammatory responses, and cytotoxicity 12 . It has also been found that ZnO NPs could reach the brain after oral and inhalatrory administration in animals 13 14 , induce the changes in the spatial learning and memory ability of rats by altering the synaptic plasticity 15 , and interact diversely with plasma and brain proteins during inducing their toxic effects in the blood and brain 16 . In vitro studies, ZnO NPs showed the strongest toxicity for mice brain tumor cell lines (Neuro-2a) when compared with similar sized particles of Al 2 O 3 , TiO 2 , Fe 3 O 4 and CrO 3 17 , decreased the activity of mice neural stem cells and human SHSY5Y neuronal cells by inducing DNA damage and cell apoptosis 18 19 , and induced apoptosis in primary cultured astrocytes through JNK signaling pathway 20 .…”
mentioning
confidence: 99%
“…Recently, there have been reports that NPs can reach the brain via blood-brain barrier (BBB) penetration and subsequently cause damage by the induction of oxidative stress, inflammatory responses, and cytotoxicity [1][2][3][4]. It has also been found that ZnONPs could reach the brain after oral administration in animals or translocation along the olfactory nerve pathway [5,6] and may induce the changes in the spatial learning and memory ability of rats by altering the synaptic plasticity [7], and induce toxic effects in the blood and brain [8]. Earlier, ZnONPs have shown toxicity in mice brain tumor cell lines (Neuro-2a) when compared with similar sized particles of Al 2 O 3 , TiO 2 , Fe 3 O 4 , and CrO 3 [9].…”
Section: Introductionmentioning
confidence: 99%